(untitled) (Journal of Tourism & Adventure, 2019)
The topic of Quality of Life (QoL) has received increased research attention in recent research years as tourism development should contribute to the wellbeing of destination communities and those who are employed by the tourism industry. The consideration of younger employees that is the millennial work force is important globally but also for Small Island developing states with challenges of small population size and migration of the younger generation seeking better job opportunities abroad. To be prepared for the future, the tourism sector needs to understand and adapt to this younger workforce and investigate how they perceive their Quality of Work Life (QWL) and its impacts on their well-being. Examining how tourism contributes to QoL is important to better plan for tourism so as to support the prosperity of the population, industry and destination. Nevertheless, limited research has investigated QWL and QoL. The objectives of this study are to firstly examine the impact of QWL and QoL; secondly, to investigate the relationship between QWL and support for future tourism development and thirdly to examine the relationship between QoL and support for future tourism development. A mixed method approach with unstructured interviews and 400 questionnaires were used to investigate the issue. This study found that a relationship exists between QWL, QoL and support for tourism amongst millennial, and that age of the employees influenced this correlation.